2018
DOI: 10.1007/s11655-018-2983-5
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Evaluation of Antitumor Activity of Ligustrum robustum, A Chinese Herbal Tea

Abstract: L. robustum inhibits tumor cell growth both in vitro and in vivo by inducing apoptosis in a caspase-dependent way without apparent hepatic toxicity and histological damage, which may offer partial scientific support for the ethnopharmacological claims of L. robustum as a herbal tea for its antitumor activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…To preparation of LR extract for component analysis, 50 g LR was ground to a fine powder and suspended in 1500 mL distilled water and incubated with shaking at 80°C for 3 h. Then the extract was filtered and further evaporated on a rotary evaporator to a concentration to 1 g/mL and stored at −20°C until further use [10]. The analytical solution was prepared by filtering 220 μ L supernatant using a 0.22 μ m filter.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To preparation of LR extract for component analysis, 50 g LR was ground to a fine powder and suspended in 1500 mL distilled water and incubated with shaking at 80°C for 3 h. Then the extract was filtered and further evaporated on a rotary evaporator to a concentration to 1 g/mL and stored at −20°C until further use [10]. The analytical solution was prepared by filtering 220 μ L supernatant using a 0.22 μ m filter.…”
Section: Methodsmentioning
confidence: 99%
“…Ligustrum robustum ( LR ), a traditional Chinese beverage plant, contains abundant bioactive compounds with health benefits, such as flavonoids, total phenolic acid, polysaccharide, and triterpenoid [6, 7]. Animal studies have shown the antiobesity, antioxidative, anti-inflammatory, antitumor, and hepatoprotective effects of LR [810]. Moreover, the LR -induced changes in the composition of gut microbiota were also observed accompanied with weight loss in an animal study [11].…”
Section: Introductionmentioning
confidence: 99%
“…It was widely demonstrated that the extract of this tea exhibits antioxidant activity and eliminates free radicals in food systems (Yu & Zeng, 2013). Moreover, it also exhibits anti‐inflammatory, antitumor, neuroprotective, and hepatoprotective activities (Chakraborty et al., 2012; Zuo et al., 2019). However, the research focus on the antimicrobial and anticaries effects of L. robustum is limited.…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, around 1.9 billion grown-ups were overweight and just about 33% were stout [13]. Ku-Ding-Cha, truly harsh spike-leaf tea, is a sort of well-known home-grown tea generally utilized in China from numerous hundred years prior [14]. They are commonly treated with a wide assortment of antifungal medications [11].…”
Section: Introductionmentioning
confidence: 99%